INTERAKSI BAHASA CERAMAH GUS MUWAFIQ DALAM ACARA MAULID NABI DI ISTANA PRESIDEN BOGOR - Bahruddin, Muhammad (sarasvati, 2019)
This research examines the interaction of language Gus Muwafiq talk in the event of a maul prophet at the presidential palace bogor but only focuses on language variations and interfering in a code adopted by Gus Muwafiq talk. The kind of research used descriptive qualitative. In this research will be elaborate about the kind of research variation language used on Gus Muwafiq talk. The research results (1) variation language used in a Gus Muwafiq in the event of a maul prophet at the palace bogor divided into four variety of, which is its diversity of official, business, relax and familiar. That fourth of its diversity of relax and familiar used most often. The diversity of is very suitable when talks due to a lector will try to catch up with the audience or an audience through a language that contains sense of humor. So that his hearers or an audience share my enthusiasm to lectures ever listens. (2) intervening code that is added to talk Gus Muwafiq in the event of a maul prophet in the palace bogor found the form of intervening code in talk gus muwafiq in the form of said, phrase , and clause.